2018
DOI: 10.1158/1078-0432.ccr-17-2899
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Transarterial Chemoembolization for HBV-Related Hepatocellular Carcinoma After Resection: A Randomized Controlled Study

Abstract: Statement of translational relevance:Disease recurrence after curative resection for hepatocellular carcinoma (HCC) patients Experimental Design:In this randomized phase 3 trial, 280 eligible patients were assigned to adjuvant TACE (n=140) or no adjuvant treatment (control; n = 140) groups.The primary endpoint was recurrence-free survival (RFS); secondary endpoints included overall survival (OS) and safety. Multivariable Cox-proportional hazards model was used to determine the independent impact of TACE on pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
227
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 216 publications
(234 citation statements)
references
References 30 publications
5
227
2
Order By: Relevance
“…Nevertheless, little is known about the mechanism of HCC metastasis. Currently, transcatheter arterial chemoembolization is the only effective adjuvant therapy with global acceptance to prevent recurrence of HCC after curative resection, but its efficiency is limited . Thus, it is necessary to find key molecules associated with HCC invasion, which might be potential therapeutic targets for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, little is known about the mechanism of HCC metastasis. Currently, transcatheter arterial chemoembolization is the only effective adjuvant therapy with global acceptance to prevent recurrence of HCC after curative resection, but its efficiency is limited . Thus, it is necessary to find key molecules associated with HCC invasion, which might be potential therapeutic targets for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous retrospective study, postoperative adjuvant TACE prolonged the survival of patients with risk factors [28,29]. In our prospective study, we found that adjuvant TACE significantly reduced tumour recurrence and improved RFS and OS in patients with HBV-related HCC who had an intermediate or high risk for recurrence [16]. Regarding ICC recurrence, ICC patients with high nomogram scores benefited from adjuvant TACE following liver resection [30].…”
Section: The Prognostic Factors Of Chc After Psmmentioning
confidence: 74%
“…Similar to HCC and ICC, for CHC, recurrence is the most adverse factor influencing OS and DFS; vascular and lymph node invasion as well as the presence of satellite metastasis have been suggested as significant predictors of poor outcome after curative resection [13][14][15]. Transarterial chemoembolization (TACE), percutaneous ethanol injection (PEI) and radiofrequency ablation (RFA) are the most widely used treatments for HCC and postresection recurrence [16][17][18]. For CHC, TACE shows an advantageous response and prognosis in recurrent patients after resection [19].…”
mentioning
confidence: 99%
“…Those patients with type III PVTT, multiple tumors, or cirrhosis were likely to derive more clinical benefit than their counterparts, indicating that PVC could reduce the risks of recurrence and death in patients with unfavorable clinicopathological factors. 18,23 Furthermore, a high HBV DNA level adversely affected survival, likely due to impaired hepatic function. Consequently, use of antiviral treatment is advisable at levels >10 4 IU/mL during PVC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Since sex, age, degree of PVTT, Edmondson stage, tumor number, tumor encapsulation, tumor size, AFP level, HCV, HBsAg, HBV DNA, AST, GGT, albumin, platelet count, PT, degree of cirrhosis, and Child-Pugh stage were potential prognostic factors for HCC patients, they were taken into consideration in the PSM analysis 23,24. To further investi-…”
mentioning
confidence: 99%